Implementasi Program Gerakan Ramah Lingkungan di Kelurahan Tangga Takat dan Kelurahan 17 Ilir Kota Palembang - Fitri Herdayani (Universitas Medan Area, 2020)
The purpose of this study was to determine the Implementation of the Environmentally Friendly Movement Program in the Stairs of Takat and 17 Ilir in Palembang. The research method in the form of qualitative research. The results of the analysis show that the implementation of the Environment Friendly Movement Program in the Takat and 17 Ilir Kelurahan in Palembang City has been carried out well, it is seen from several dimensions and indicators all of them have been implemented and responded well by the community in Tangga Takat Kelurahan and 17 Ilir Kota Kelurahan Palembang such as: the communication received by the implementers of the policy must be clearly implemented properly. The conclusion of the study is consistency, the order to implement a policy must be fixed or not changing well implemented, and cleaning up the water flow, especially in the office school environment and residents' neighborhoods alternately in each RW. The main resource in implementing the policy is the availability of staff that has been implemented well by. Information, an implementor must know what they are doing when they are given orders to carry out a policy that has been implemented well. Appointment of people who have the ability to implement established policies have been implemented well. Routine activities that are the basis for implementing policies in accordance with established standards have been implemented well.